2004
DOI: 10.1002/ajmg.b.20172
|View full text |Cite
|
Sign up to set email alerts
|

Modifier effects in autism at the MAO‐A and DBH loci

Abstract: Autism is one of a group of pervasive developmental disorders (PDD) characterized by qualitative impairments in reciprocal social communication and by a preference for repetitive, stereotyped activities, interests, and behaviors. The disorder is caused in large part by genetic mechanisms, though no disease genes have yet been identified. The objective of this study was to investigate three markers, two in the DBH gene and one in the MAO-A gene, for maternal or fetal modifier effects on level of functioning (IQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The power estimate for the prior study was 0.123 with 88 patients and 92 controls. Currently, there are more than 20 genes identified as being involved in serotonin level and serotonin effects, and polymorphism(s) in some of them have been associated with autism in some, but not other, reports [e.g., Veenstra-VanderWeele et al, 2002;Jones et al, 2004]. These genes should be investigated to explore the association of hyperserotonemia with autism and with the obsessive-compulsive behaviors and repetitive/stereotyped symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…The power estimate for the prior study was 0.123 with 88 patients and 92 controls. Currently, there are more than 20 genes identified as being involved in serotonin level and serotonin effects, and polymorphism(s) in some of them have been associated with autism in some, but not other, reports [e.g., Veenstra-VanderWeele et al, 2002;Jones et al, 2004]. These genes should be investigated to explore the association of hyperserotonemia with autism and with the obsessive-compulsive behaviors and repetitive/stereotyped symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in their 1-year follow-up testing, those with the low-activity allele showed a worsening in IQ with no change in the severity of their autistic behavior. Jones et al 16 found that maternal genotypes at the MAOA locus may modify IQ in children with autism through the intrauterine environment.…”
Section: Autism Spectrum Disorders (Asd)mentioning
confidence: 99%
“…Jones et al [2004] reported that maternal genotypes containing specific polymorphisms at the MAO-A locus showed significant negative correlations with the intelligence quotient (IQ) in children with autism. These results are consistent with those of Cohen et al [2003], who found that a low-activity MAO-A allele (due to an upstream variable-number tandem repeat region) is associated with both lower IQ and more severe autistic behavior in children, as compared to the high-activity allele.…”
Section: Altered Prenatal Serotonin-evidence For a Role In Autismmentioning
confidence: 99%